Training affects knee kinematics and kinetics in cutting maneuvers in sport - Cochrane, J. L.; Lloyd, D. G.; Besier, T. F.; Elliott, B. C.; Doyle, T. L. A.; Ackland, T. R. (Medicine & Science in Sports & Exercise, 2010)
Purpose: The current study examined how different training affects the kinematics and applied moments at the knee during sporting maneuvers and the potential to reduce loading of the anterior cruciate ligament (ACL). The training programs were 1) machine weights, 2) free weights, 3) balance training, and 4) machine weights + balance training.